Changing by the Click: The Professional Development of UK Journalists - Colm Murphy (MDPI AG, 2019)
Changes in technology, audience engagement, the business model and ethical requirements have greatly expanded the skills required to be a professional journalist in the UK. At the same time, the esteem in which the profession is held by the public has diminished. This research used the UK journalism profession as a case study of change in a profession. It asked what were the changes in the profession since 2012. The research method includes an in-depth survey of 885 UK journalists, two previous similar surveys, interviews with stakeholders, national data and documentation. The study finds that UK journalist numbers, their educational attainment and workload has increased significantly in the period. The majority have become multiplatform journalists-working across at least two mediums like print and online. There has been a significant shift of job roles from traditional newsroom to a wide range of other organizations and some 36% of journalists are now self-employed. Diversity continues to be an issue with the profession having a white middle-class bias. The implications of these changes for future professional UK journalism education were then analyzed. They include the need to develop a national continuous professional development framework, better cooperation amongst competing accrediting bodies to enhance the public trust in journalists and greater flexibility on the professional pathways to senior qualifications.